Justice, Conflict and Development - Jensen, Erik (World Bank, Washington, DC, 2018)
Access to justice is a 'big tent' for law programs broadly writ and has been so for over 25 years. Traditionally, access to justice has been treated as a category of interventions rather than a heuristic device from which to learn and experiment. In the old, old days, access to justice meant legal aid, support for narrow categories of human rights cases (so-called test case litigation), discrete support for formal legal institutions, and at least through The Asia Foundation and Ford Foundation discrete support for community based mediation and nascent civil society groups that supported paralegals.